2005
DOI: 10.1002/star.200400386
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Starch‐rich Powders Prepared by Autoclaving of Native and Lintnerized Banana Starch: Partial Characterization

Abstract: Powdered preparations enriched in resistant starch (RS) were obtained from native and lintnerized (prolonged acid treatment) banana starches by consecutive autoclaving/cooling treatments. The preparations were tested for indigestible starch content, swelling and solubility properties, thermal analysis and pasting profile. The autoclaved samples had higher RS content than their parental counterparts, but the chemical modification (lintnerization process) allowed development of higher RS proportions (19%, dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
78
4
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 17 publications
10
78
4
7
Order By: Relevance
“…Teknik modifikasi peningkatan pati resisten dengan siklus autoclaving-cooling telah dilaporkan oleh banyak peneliti, seperti Aparicio-Saguilan et al (2005), Gonzalez-Soto et al (2007), Zabar et al (2008), Sugiyono et al (2009), Vatanasuchart et al (2012, Asbar (2014). Prinsip dari teknik tersebut adalah pati disuspensikan dahulu dalam air dengan nisbah penambahan air tertentu (1:21:5).…”
Section: Teknik Pemanasan Bertekanan Dan Pendinginan (Autoclaving-coounclassified
See 1 more Smart Citation
“…Teknik modifikasi peningkatan pati resisten dengan siklus autoclaving-cooling telah dilaporkan oleh banyak peneliti, seperti Aparicio-Saguilan et al (2005), Gonzalez-Soto et al (2007), Zabar et al (2008), Sugiyono et al (2009), Vatanasuchart et al (2012, Asbar (2014). Prinsip dari teknik tersebut adalah pati disuspensikan dahulu dalam air dengan nisbah penambahan air tertentu (1:21:5).…”
Section: Teknik Pemanasan Bertekanan Dan Pendinginan (Autoclaving-coounclassified
“…Proses autoclaving-cooling secara berulang dapat menyebabkan semakin banyaknya pembentukan fraksi amilosa teretrogradasi atau terkristalisasi (Aparicio-Saguilan et al 2005). Fraksi amilosa yang berikatan dengan fraksi amilosa lainnya melalui ikatan hidrogen membentuk struktur double helix.…”
Section: Teknik Pemanasan Bertekanan Dan Pendinginan (Autoclaving-coounclassified
“…Heat moisture treatment consists of autoclaving-cooling and cross-linking can be applied to obtain resistant starches and improve the yield of resistant starches (Abdoulaye et al 2012;Aparicio-Saguilan et al 2005;Onyango et al 2006). The bihon dough is made from 5% pregelatinized starch (acting as the gluten in wheat flour dough) mixed with 95% of the remaining (native) starch and water to a dough.…”
mentioning
confidence: 99%
“…RS is classified to type I (inaccessible starch in a cellular matrix), type II (native uncooked starch granules that form crystalline, and make them difficult to hydrolysis), type III (retrograded starch, which be formed in cooked), type IV (chemical modified starches) [4]. Nowadays, the scientists interest of RS formation especially utilization of RS in food production.…”
Section: Introductionmentioning
confidence: 99%
“…This method increases crystalline content, which becomes resistant by enzymatic hydrolysis. Reference [4] has investigated that resistant banana starch is obtained 16% from this method, and then autoclaved, its shows a lower solubility in water than native starch and RS value is higher than only lintnerized treatment. Besides that, Aparicio's research [4] has showed that resistant starch prepared by lintnerizedautoclaved contained slowly digestible carbohydrate.…”
Section: Introductionmentioning
confidence: 99%